Posicionamento: a marca UFU no Instagram por meio de notas oficiais - Santos, Jussara Paola Coelho dos (2024)
This dissertation deals with institutional communication by official statement on social media as brand positioning seeking to analyze these are reinforcing what is described in the corporate identity of a public education institution. As an object of analysis, Instagram posts from the Federal University of Uberlândia (UFU) were used during the first academic semester of 2021/2, which corresponds to the months of May to August 2022. The study was divided into 4 parts. The first use was concepts relating to the internet and digital media. The second focused on discussion, concepts and criteria of organizations and communication, the third discusses and categorizes brand and branding principles. The fourth part of this work creates a matrix for brand positioning analysis based on the concepts discussed in the previous chapters that can be used by university managers and other researchers who aim to investigate whether practical communication, through official notes, is aligned with corporate identity. within the situations and reaches a conclusion about the object, the posts of UFU's official notes on Instagram. The results clearly indicate that the UFU brand follows its brand identity when writing its official notes, but that this identity needs to be revisited by managers for an update to align with organizational dimensions in the contemporary context. Adapting to new trends through rebranding.